Churg-Strauss syndrome with critical endomyocardial fibrosis: 10 year survival after combined surgical and medical management. Issue 5 (1st May 2002) - McGavin, C R; Marshall, A J; Lewis, C T
Abstract : A case is presented of the Churg-Strauss syndrome with hypereosinophilia and severe cardiac involvement, namely biventricular endomyocardial fibrosis and gross encroachment of the right ventricular cavity. The clinical picture was similar to Loeffler's syndrome and the idiopathic hypereosinophilic syndrome. Combined aggressive surgical and medical management led to full recovery and survival at 10 years. The good long term outcome is attributed to strict control of peripheral eosinophil count by oral corticosteroids. This case illustrates the damaging effects of hypereosinophilia on the heart.